2018
DOI: 10.3892/mmr.2018.9787
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑219 overexpression serves a protective role during liver fibrosis by targeting tumor growth factor β receptor 2

Abstract: Progressive liver fibrosis is the primary cause of liver cirrhosis and hepatocellular carcinoma, and leads to considerable morbidity and mortality. Recent studies have demonstrated that microRNAs (miRNAs or miRs) are associated with fibrotic processes in liver disorders, although the exact role of miR-219 remains unclear and the relevant mechanisms remain to be completely understood. To the best of our knowledge, the present study was the first to demonstrate the functional implications of miR-219 expression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Similarly, bladder fibrosis is thought to be involved in BSMC activation and excess extracellular matrix accumulation. Some studies have shown that miRNAs are involved in smooth muscle cell function, including cell proliferation, the cell cycle, and apoptosis [ 23 , 28 , 29 ]. There is growing evidence that many miRNAs play key regulatory roles in bladder fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, bladder fibrosis is thought to be involved in BSMC activation and excess extracellular matrix accumulation. Some studies have shown that miRNAs are involved in smooth muscle cell function, including cell proliferation, the cell cycle, and apoptosis [ 23 , 28 , 29 ]. There is growing evidence that many miRNAs play key regulatory roles in bladder fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that miRNAs are involved in smooth muscle cell function, including cell proliferation, the cell cycle, and apoptosis. [23,28,29] There is growing evidence that many miRNAs play key regulatory roles in bladder brosis. LJ et al [30] demonstrated a novel miR-133 regulatory factor that targets the TGF-β-Smad3 signaling pathway to modulate TGF-β1induced changes in the BSMC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that miRNAs are involved in smooth muscle cell function, including cell proliferation, the cell cycle, and apoptosis. [23,28,29] There is growing evidence that many miRNAs play key regulatory roles in bladder brosis. LJ et al [30] demonstrated a novel miR-133 regulatory factor that targets the TGF-β-Smad3 signaling pathway to modulate TGF-β1-induced changes in the BSMC phenotype.…”
Section: Discussionmentioning
confidence: 99%